Methods for fabricating isolated micro- and nano- structures using soft or imprint lithography (2013)
The presently disclosed subject matter describes the use of fluorinated elastomer-based materials, in particular perfluoropolyether (PFPE)-based materials, in high-resolution soft or imprint lithographic applications, such as micro- and nanoscale replica molding, and the first nano-contact molding of organic materials to generate high fidelity features using an elastomeric mold. Accordingly, the presently disclosed subject matter describes a method for producing free-standing, isolated nanostructures of any shape using soft or imprint lithography techniques.